2020
DOI: 10.1029/2020gl087645
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Electrical Conductivity of Marine Gas Hydrate

Abstract: Methane hydrate was synthesized from pure water ice and flash frozen seawater, with varying amounts of sand or silt added. Electrical conductivity was determined by impedance spectroscopy, using equivalent circuit modeling to separate the effects of electrodes and to gain insight into conduction mechanisms. Silt and sand increase the conductivity of pure hydrate; we infer by contaminant NaCl contributing to conduction in hydrate, to values in agreement with resistivities observed in well logs through hydrate‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…(2019) and Constable et al. (2020) in which ECM fitting was performed using EIS Spectrum Analyzer software (Bondarenko & Ragoisha, 2005). Briefly, the ECM fits indicate that different conduction mechanisms exist for CH 4 hydrate assemblages (i.e., CH 4 hydrate with impurities, sediments, or fluids present) at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(2019) and Constable et al. (2020) in which ECM fitting was performed using EIS Spectrum Analyzer software (Bondarenko & Ragoisha, 2005). Briefly, the ECM fits indicate that different conduction mechanisms exist for CH 4 hydrate assemblages (i.e., CH 4 hydrate with impurities, sediments, or fluids present) at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in controlled‐source EM technology now allows measurement of even small variations in conductivity; for example, Kannberg and Constable (2020) resolved seafloor conductivity by a factor of two. We have previously demonstrated that EM studies in the field can benefit from salinity‐conductivity insights gained from laboratory measurement of σ on pure CH 4 hydrate and hydrate ± variable amounts of ionic impurities, sediments, or brines (Constable et al., 2020; Du Frane et al., 2011, 2015; Lu et al., 2019). Our measurements of methane hydrate formed in the presence of NaCl, for example, compare well with field measurements from logging‐while‐drilling data collected from seafloor chimneys off eastern Japan containing high saturations of gas hydrate (Matsumoto et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations